Decolonial feminisms and degrowth. (February 2022) - Abazeri, Mariam
Highlights: Gender, race, and labor are fundamentally tied to the development of modern capitalist global systems. This relation must be central in the understanding and praxis of non-capitalist alternatives. Decolonial feminisms reimagines intersubjective knowledges, practices, and relations away from modern colonial gender systems. Through decolonial feminist praxis, degrowth can better address, dislodge, and reimagine the relations that maintain an ideology of growth. Abstract: Degrowth has become a major topic of interdisciplinary scholarship and practice that critiques the ideology of growth, reimagining social and economic relations and measures of well-being outside economic rationality. While the movement engages with gender politics peripherally in coalition with feminist schools of thought and activist groups, e.g., the feminisms and degrowth alliance, I argue the politics of gender, race, and labor are fundamentally tied to the development of a modern capitalist global system and therefore must be central in the understanding and praxis of non-capitalist alternatives. In this article, I examine how a decolonial feminist approach can address this condition by challenging the epistemes and ontologies that constitute modern colonial systems of power and furthering plural understandings and practices of being, seeing, and knowing across the North-South divide. By engaging in decolonial feminist praxis, degrowth stands to better address, dislodge, and reimagine the elements and relations that maintain an ideology of growth, building instead towards a stronger coalition across movements that encourages socially just and ecologically sustainable futures.